Optimization of the product delivery system for a company in the building material sector - Örkün, Didem. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2009., 2009)
Effective management of logistics activities is crucial for companies. Previous studies have shown that transportation costs constitute an important part of the overall expenses. Therefore, companies solely focusing on new customer acquisition and product portfolio enlargement realize that not paying the necessary attention to manage the operational processes, in particular logistics activities, threaten their existence. Eczacıbaşı İntema has recently adopted the strategy of providing service through its retail channel which consists of its own stores. Aiming at growing through this new distribution channel required to review its old business attitudes and to reorganize its internal processes in a way to support customer-driven business making. During this switch period, the company noted that end customers’ complaints and problems are now a part of their business as a result of building direct relationship with customers. Therefore, the review of customer order patterns, current sales in the cities per customers and per stores as well as detection of improvement domains became a priority. Upon the request of the company, we initiated this study to examine the company’s current situation with the problems and challenges coming from the business and to develop solutions and improvements regarding cost cutting possibilities and customer satisfaction. In this study, we make an effort to solve the real-world problem by developing a model to satisfy the needs of İntema, i.e., reducing the cost, increasing the customer satisfaction and effective use of resources. With the focus on the product delivery system, a detailed current situation analysis is performed to define the challenges and the constraints preventing İntema to move ahead confidently. Then, a delivery planning model is proposed. This suggested model produces better results compared to the existing business model under the assumptions given in the study and ensures some important cost savings.
Keywords: Delivery of goods.; Building materials industry.